Effects of seaweed-based bio-stimulant kelpak© on chilling injury incidence in tomato (solanum lycopersicum L) fruit during postharvest cold storage - Musarurwa, Calvin Kudakwashe (My University, 2025)
Refer to document
Thesis (M. Agriculture Management (Plant Production)) -- University of Limpopo, 2025
Keywords: Seaweed; Biostimulant kelpak; Tomato; Marine algae; Tomato growers; Cold storage